A study of 74 cases of brain Abscess - AL-Shalchy, Ali. K. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Brain abscess is collection of pus in the brain parrynchima surrounded by a true capsule. Usually diagnosed by CT & MRI, & treated surgically by drainage by burr hole, or excision. Objective: evaluate our work with brain abscess. Patient& method: 74 Patients collected in the specialized surgical hospital neuro-surgical department, from Jan. 1995 till Jan. 2005 treated surgically, all cases fully evaluated clinically & radiologically & then evaluation of the surgical procedure. Results: there is a slight male predominance & prevalence more in the 1st 2decades of life mostly in children with cong. heart disease, headache was the most common presenting feature, with other signs of infection diagnosis was mostly by CT scan, all cases were managed surgically & the out come is compared other studies. Conclusion: Brain abscess a relatively common disease, each case should be managed individually & depending on surgeon experience.